Multiloculated peritoneal inclusion cyst in male patient: a case report - Kankariya, Jeevan; Bansal, Shubham (International Surgery Journal, 2022)
Multilocular peritoneal inclusion cyst (MPIC), also known as benign multicystic peritoneal mesothelioma, is a rare mesothelial lesion arising from the peritoneal mesothelium. This condition most commonly occurs in females of reproductive age group and are very rare in males. We report a case of young male patient, presented with the chief complaint of lower abdominal pain, without any previous history of surgery. After radiological investigations which were suggestive of pelvic inclusion cysts, pt. was planned for diagnostic laparoscopy (D/L). On D/L, multiple free-floating cysts were found in pelvis between rectum and bladder which were successfully extracted and sent for histopathological examination (HPE). HPE confirmed it to be MPIC.